STRATEGI KOMUNIKASI KPU SUKOHARJO DALAM MENGURANGI GOLPUT PEMILU CAPRES CAWAPRES 2024 PADA KALANGAN GEN Z - Muhtaram, Khalish Ariq; Suryo Sarjono, Herning; Kusumo Aji, Haryo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
According to KPU data, the abstention rate in the 2014 elections in Indonesia is still relatively high, namely 49,212,161 (29.1%) out of 176,411,434 permanent voters. The low political participation of the Indonesian people is caused by several factors. One of them is the lack of election education and also the high abstention rate. The data from the SUKOHARJO KPU states that community participation in elections has increased to 80% and the abstention rate has decreased to 4%, while this increase is not accompanied by a decrease in abstention among gen Z In Sukoharjo Regency, which actually experienced an increase in abstention of 2.21% from 2014 to 2019 in the presidential election contestation.The research was conducted with the aim of the communication strategy formed by the Sukoharjo KPU in order to reduce the abstention rate of the 2024 presidential and vice presidential elections among the Z generation. In a process of implementing this research, data collection methods were carried out through interviews with informants. The informants selected were 6 people who were representatives of the Sukoharjo Regency KPU staff. Data is analyzed and conclusions are drawn qualitatively without numbers. Data validity is proven by direct interactive with data sources (Source Triangulation). The results of the conclusion show that the communication strategy carried out by the KPU (General Election Commission) of Sukoharjo Regency in order to reduce the abstention rate for the 2024 presidential and vice presidential elections among the Gen Z generation is carried out with 3 strategic steps. That is the socialization of the importance of elections, maximizing the use of social media owned and working on online campaigns (online pamphlets and political education videos). Where from the three strategic steps of the Sukoharjo KPU, all of which fulfill the occurrence of a good communication strategy as quoted according to Harold Lasswell's communication theory (1948). KPU's communication strategy fulfills the 5 elements of Who, Says What, In Which Channel, To Whom, With What Effect.